Transfer of Hexon‐ and Penton‐selected adenovirus‐specific T cells for refractory adenovirus infection after haploidentical stem cell transplantation. Issue 1 (11th November 2019) - Schultze‐Florey, Rebecca E.; Tischer‐Zimmermann, Sabine; Heuft, Hans‐Gert; Priesner, Christoph; Lamottke, Britta; Heim, Albert; Sauer, Martin; Sykora, Karl‐Walter; Blasczyk, Rainer; Eiz‐Vesper, Britta; Maecker‐Kolhoff, Britta
Abstract: Adenovirus (HAdV) infections confer a high risk of morbidity and mortality for immunocompromised patients after stem cell transplantation (SCT). Treatment with standard antiviral drugs is of limited efficacy and associated with a high rate of adverse effects. HAdV‐specific T cells are crucial for sustained viral elimination and the efficacy of adoptive T‐cell therapy with donor‐derived HAdV‐specific T cells has been reported by several investigators. Here, we report our experience with the transfer of HAdV‐specific T cells specific for penton, which was recently identified as an immunodominant target of T cells, and hexon in a 14‐year‐old boy after T‐cell‐depleted haploidentical SCT for myelodysplastic syndrome (MDS). He developed severe HAdV‐associated enteritis complicated by acute graft‐versus‐host disease (GvHD). The patient received ten infusions of allogeneic HAdV‐specific T cells manufactured from the haploidentical stem cell donor using the CliniMacs Interferon‐γ (IFN‐γ) cytokine capture and immunomagnetic selection. Initially, T cells were generated against the immunodominant target hexon and in subsequent transfers dual antigen‐specific T cells against hexon and penton were applied. T‐cell transfers were scheduled individually tailored to current immunosuppressive treatment. Each transfer was followed by reduction of HAdV load in peripheral blood and clinical improvement. Importantly, T‐cell responses to both penton and hexon pools emerged in patient blood after repetitive transfers. Unfortunately, the patient experienced bacterial sepsis, and in this context, severe GvHD requiring intensive immunosuppression followed by secondary progression of HAdV infection. The patient succumbed to multiorgan failure 283 days after SCT. This case demonstrates the feasibility of HAdV‐specific T‐cell transfer even in the presence of immunosuppressive treatment. Targeting of multiple immunodominant viral proteins may prove valuable in patients with complicated HAdV infections.